Ecological justification for the formation of a regional ecological network for determining the directions of functioning of riverside zones. Theory and practice - Макеєва, О. В. (Scientific Progress & Innovations, 2018)
The current state of Ukraine’s natural landscapes partially meets the criteria for referring them to the General European Ecological Network. Deteriorating conditions for securing the territorial unity of sites with natural landscapes that make it difficult and sometimes impossible to make spatial biological exchange processes that are inherent in living nature. Based on the results of survey methods, the place, role and current state of development of regional ecological networks have been studied and described within the framework of the national program for the formation of the national ecological network of Ukraine for 2000–2015. The main principles of econetwork formation and their application at different stages of the program implementation are covered. A model for expanding the ecological network by functioning riverine zones was offered, having adopted the ecosystem of the Poltava riverine park in an ecologically stable functioning territory in a city where it is important not only to preserve the biocenosis but also to reserve and continue to grant status as a typically unique ecosystem based on stability indicators.